Differential shell strength of Cepaea nemoralis colour morphs—implications for their anti-predator defence - Rosin, Zuzanna M. (Springer Berlin Heidelberg, 2013)
One of the most spectacular evolutionary forces is predation, evidenced to stimulate polymorphism in many prey species. Shell colour polymorphism of the land snail Cepaea nemoralis is a well-known model in evolutionary research. Nevertheless, the knowledge on the ecological causes driving its evolution remains incomplete and proximal factors shaping predatory pressure on C. nemoralis morphs are unknown. We evaluated shell crushing resistance and thickness, constituting crucial snail anti-predator defences in two shell areas (the apex and labium) of eight C. nemoralis morphotypes differing in shell colour and banding pattern. A GLM showed a significant effect of shell colour, banding pattern and shell thickness on shell strength. Pink shells were stronger than yellow ones, and banded forms had stronger shells than unbanded snails. The labium (usually attacked by mice) was generally thicker and more resistant than the apex (usually crushed by birds). Thicker shells were more resistant to crushing, and the rate of shell strength increase per unit of shell thickness was greater in pink and banded individuals compared to yellow and unbanded ones. Yellow and unbanded morphs have been found to be preferred by mice in the previous studies, which suggests that shell strength may be an important trait used in prey selection by these shell-crushing predators. The differences in potential anti-predator defences among snail morphs, found in the present study, justify future research on direct effect of C. nemoralis morphs shell strength on predator selectivity.